Forests and trees for social adaptation to climate variability and change - Pramova, E.; Locatelli, Bruno; Djoudi, H.; Somorin, O.A. (Wiley, 2012)
Ecosystems provide important services that can help people adapt to climate variability and change. Recognizing this role of ecosystems, several international and nongovernmental organizations have promoted an ecosystem‐based approach to adaptation. We review the scientific literature related to ecosystem‐based adaptation (EBA) with forests and trees, and highlight five cases in which forests and trees can support adaptation: (1) forests and trees providing goods to local communities facing climatic threats; (2) trees in agricultural fields regulating water, soil, and microclimate for more resilient production; (3) forested watersheds regulating water and protecting soils for reduced climate impacts; (4) forests protecting coastal areas from climate‐related threats; and (5) urban forests and trees regulating temperature and water for resilient cities. The literature provides evidence that EBA with forests and trees can reduce social vulnerability to climate hazards; however, uncertainties and knowledge gaps remain, particularly for regulating services in watersheds and coastal areas. Few studies have been undertaken on EBA specifically, but the abundant literature on ecosystem services can be used to fill knowledge gaps. Many studies assess the multiple benefits of ecosystems for human adaptation or well‐being, but also recognize trade‐offs between ecosystem services. Better understanding is needed of the efficiency, costs, and benefits, and trade‐offs of EBA with forests and trees. Pilot projects under implementation could serve as learning sites and existing information could be systematized and revisited with a climate change adaptation lens. WIREs Clim Change 2012, 3:581–596. doi: 10.1002/wcc.195This article is categorized under: Climate, Ecology, and Conservation > Modeling Species and Community InteractionsClimate, Ecology, and Conservation > Modeling Species and Community Interactions